Church and world: Eusebius's, Augustine's, and Yoder's interpretations of the Constantinian shift - Schmidt, Simon P. (Princeton theological monograph series, 2020)
The Constantinian shift--an introduction -- An early interpretation -- A corrective -- A current interpretation -- Perspectives.